The School Librarian’ s Education and Job Profile in Croatia - Lasić-Lazić, Jadranka; Banek Zorica, Mihaela (2007)
Since Croatia is a transitional country, it is subject to many changes, in education as well as the economy. Present changes can be observed at all levels of education, from the primary schools to the universities. Their aim is to improve quality and efficiency of education. The central principle of these efforts is to develop lifelong learners with intellectual abilities of reasoning, critical thinking, creative problem-solving, decision-making, independent learning and the responsible consume of information. In elementary schools we have implemented Croatian National Educational Standard whose aims correspond to the objectives that dominate the educational sector in the EU and are directed at building a knowledge-based society in which the school system is primarily intended to prepare pupils for lifelong learning. Reform aspirations in tertiary education, inaugurated by the Bologna agreement, refer to employability, quality assurance, mobility, compatibility and imply lifelong learning as a core concept. These principles have stimulated universities to restructure their curricular offerings and bring them in line with societal needs that predominate in the knowledge economy. This change will enable exchange of both European and Croatian experts and students. These changes have influenced the education of school librarians as well as the changes in educational environment i.e. educational practice influenced by advanced technology. Authors give an analysis of the current situation in education of Croatian school librarians.
Projekt MZOS
ENG